2019
DOI: 10.2147/ccid.s216222
|View full text |Cite
|
Sign up to set email alerts
|

<p>VYC-12 Injectable Gel Is Safe And Effective For Improvement Of Facial Skin Topography: A Prospective Study</p>

Abstract: ObjectiveEvaluate safety and effectiveness of VYC-12 (Juvéderm Volite; an injectable crosslinked hyaluronic acid gel designed to improve skin quality attributes such as surface smoothness and hydration) for facial intradermal injection.Materials and methodsIn a prospective, single-arm study, subjects with moderate/severe cheek skin roughness per Allergan Skin Roughness Scale (ASRS) received VYC-12 in the cheeks and forehead, and/or neck, with touch-up treatment to correct asymmetry 30 days later and optional r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
4
5

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(76 citation statements)
references
References 26 publications
1
66
4
5
Order By: Relevance
“…Even denser crosslinking is present in Juvéderm Volbella XC (15 mg/mL), which is manufactured with a higher proportion of low molecular weight HA and designed for lip augmentation and perioral rhytids [29] . Juvéderm Volite, the least concentrated variety at 12 mg/mL, is for superficial cutaneous depressions and fine lines [30] .…”
Section: Varieties Of Hyaluronic Acid Fillermentioning
confidence: 99%
“…Even denser crosslinking is present in Juvéderm Volbella XC (15 mg/mL), which is manufactured with a higher proportion of low molecular weight HA and designed for lip augmentation and perioral rhytids [29] . Juvéderm Volite, the least concentrated variety at 12 mg/mL, is for superficial cutaneous depressions and fine lines [30] .…”
Section: Varieties Of Hyaluronic Acid Fillermentioning
confidence: 99%
“…Other studies have found evidence of objective skin quality improvement after using a new cross-linked injectable product (VYC-12 HA; Juvéderm Volite, Allergan) via digital photographic analysis. 11,12 This quality improvement effect can last up to 6 months, and the hydration retention effect can last for as long as 9 months after a single injection treatment.…”
Section: Improvement In Skin Qualitymentioning
confidence: 99%
“…Various injectable filler material, such as poly-L-lactic acid (PLLA), hyaluronic acid (HA), and hydroxylapatite, have shown the ability to induce new collagen formation after injection, thereby improving skin thickness or skin quality. 7 8 9 10 11 12 13 In this short review, the author will examine the current evidence and possibilities for treatment, and draw from personal experience to formulate expert recommendations, focusing on HA filler injections in particular.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike typical "volumetric" fillers, skinboosters are intended for the injection into more superficial (intradermal vs. deep dermis-periosteum) skin layers and are expected to improve skin appearance and texture rather than performing by a projection effect. Specifically, improvement in skin hydration and elasticity, and possibly a boost in extracellular matrix molecules biosynthesis is claimed after the application of such gels [28][29][30][31][32][33]. A stretching effect, referring to wrinkle distension from gel hydration, that is anyway filling the volume loss to a certain extent, is also predicted [30].…”
Section: Introductionmentioning
confidence: 99%